1988
DOI: 10.1071/zo9880357
|View full text |Cite
|
Sign up to set email alerts
|

The Digestion of Pollen by Some Australian Birds

Abstract: About one-third of all banksia pollen grains excreted 1-2 hours after ingestion by captive New Holland honeyeaters (Phylidonyris novaehollandiae), zebra finches (Poephila guttata) and budgerigars (Melopsittacus undulatus), had lost their protoplasmic contents. Most pollen passed through the digestive systems of these birds in 4-5 hours and up to 44% of grains were digested. The faeces of wild purple- crowned lorikeets (Glossopsitta porphyrocephala) showed a similar proportion of empty grains. In the budgerigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…This level of pollen grain emptying is similar to that seen in field studies of Purple-crowned Lorikeets (Wooller et al 1988). This rate of pollen grain emptying is relatively low compared to that found in honey possums (95-100%).…”
Section: Discussionsupporting
confidence: 71%
“…This level of pollen grain emptying is similar to that seen in field studies of Purple-crowned Lorikeets (Wooller et al 1988). This rate of pollen grain emptying is relatively low compared to that found in honey possums (95-100%).…”
Section: Discussionsupporting
confidence: 71%
“…Pollen ingestion requires less energy than insect feeding, as pollen will be encountered while foraging on nectar. However, birds vary in their ability to extract nutrients from pollen, hummingbirds being less efficient than some other nectarfeeders (Wooller et al 1988, Brice et al 1989, Richardson and Wooller 1990, Van Tets and Nicolson 2000. Pollen protein constituents also vary between plant groups, with some essential amino acids lacking (Martı´nez del Rio 1994), perhaps limiting the usefulness of pollen as a diet component.…”
Section: Nitrogenmentioning
confidence: 99%
“…To test this assumption it is necessary to compare animals that differ in their natural feeding habits under the same experimental conditions. For example, Woller et al (1988) found that specialized and non-specialized avian pollen feeders do not differ in their ability to extract pollen contents, but they did not use the same species of pollen for the comparison. To date, the only controlled study that compared the extraction efficiency of pollen grains in animals with different pollen use was conducted with phyllostomid bats (Herrera and Martı´nez del Rio 1998).…”
Section: Introductionmentioning
confidence: 97%